(untitled) (Pedagogy of Higher and Secondary Education, 2007)
In article questions of conditions of formation of the creative person of the singer, the conductor, the teacher of music are considered during singing-choral preparation on system of credit-modular training; a parity of the contents, the organization of vocational training to work from a mansion.